PERBANDINGAN EFEK TERAPETIK CEFIXIME DALAM SEDIAAN GENERIK DAN BRANDED PADA PASIEN DENGAN INFEKSI SALURAN PERNAPASAN BAGIAN BAWAH - , Yane Dila Keswara ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Bronchitis and pneumonia are lower respiratory infection that can be caused by bacteria and often occur in children. Drug product of cefixime,generic and branded,are widely used in Rajawali Citra Hospital. The use of generic for the treatment of a disease is often questionable in terms of effectiveness when compared to branded. The aim of this research is to determine the difference between therapeutic effect of generic cefixime and branded cefixime based on the clinical monitoring after the patients taking antibiotics. This study was a quasi-experimental study with prospective data collection in pediatric department Rajawali Citra RS Yogyakarta. The subjects who fulfillinclution criteria were divided into two groups: generic cefixime group (group A) and branded cefixime group (group B). Parameters that observed were duration disappearance of fever, cough, cold, and other symptoms. Data were analyzed using unpaired studentâs t-test with a level of 95%. The average of fever disappearance duration in each group are not statistically different (p >0.05). The average of fever disappearance duration in group A is 3.30 days and 3.16 days in group B. The disappearance duration of cough in each group are not statistically different (p>0.05). The average of cough disappearanceduration in group A is 5.92 days and 5.84 days in group B. The disappearance duration of cold in each group are not statistically different (p >0,05). The average of cold disappearance duration in group A is 5.89 days and 5.95 days in group B. The disappearanceduration of other symptoms in each group are not statistically different (p > 0,05). The average of other symptom disappearanceduration in group A is 3.0 days and 3.05 days in group B. There were no differences therapeutic effects between generic cefixime and branded cefixime based on the observed patient's clinical symptoms. Disappearance of fever, cough, cold, and other symptoms in both groups had the duration (days) were almost the same.